The Differences of Abdominal Stretching Exercises and Warm Compresses on the Intensity of Menstrual Pain (Dysmenorrhea) in Young Women in Jember Midwifery Program - indah luthfia wahyuni (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2018)
Wahyuni, Indah, 2018. The difference of Abdominal Stretching Exercises and Warm Compresses on the Intensity of Menstrual Pain (Dysmenorrhea) in Young Women in Jember Midwifery Program. Essay. Main Advisor: Susilawati, SST., M.Kes. Counselor: Gumirarti, SST., MPH. Dysmenorrhea is one of the problems that teenagers often experience during menstruation, and even dysmenorrhea can lead to reduced physical activity in adolescents. Not infrequently many teens to have to rest and leave the activity because of severe pain. Non-pharmacological methods that can reduce the pain of dysmenorrhea is the practice of abdominal stretching and warm compresses. The purpose of this study To determine the differences in the effectiveness of abdominal stretching exercises and warm compresses against the intensity of menstrual pain (dysmenorrhea) in young women. This research method used a quasi-experiment research design using a non-equivalent pretest-posttest design. Sampling by way of probability sampling with Simple Random Sampling with the number of samples counted 26 respondents. The instrument used is the Measure of Pain Scale (VDS). Data analysis using Independent T-Test. The results showed an average of dysmenorrhea pain after being given abdominal stretching exercise 2,1333. The average dysmenorrhea pain after a warm compression of 2.0625. So it can be concluded that there is no difference in abdominal stretching exercises and warm compresses to the intensity of menstrual pain in adolescents in Prodi DIV midwifery Jember in 2018. Both methods are effective to reduce dysmenorrhea pain. It was expected that adolescents can perform abdominal stretching exercises and warm compresses to reduce dysmenorrheal pain and provide information on abdominal stretching exercises and warm compresses to other dysmenorrhoea relatives or relatives to reduce dysmenorrheal pain. Keywords: abdominal stretching exercises, warm compresses, dysmenorrhea